2014
DOI: 10.1016/j.nbd.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hypoxia increases vulnerability of hypoxic–ischemic brain injury in neonatal rats: Role of glucocorticoid receptors

Abstract: Gestational hypoxia is a common stress to the fetal development and increases the risk of neonatal morbidity. The present study tested the hypothesis that fetal hypoxia results in heightened brain vulnerability to hypoxic-ischemic (HI) injury in neonatal rats via down-regulation of glucocorticoid receptor (GR) in the developing brain. Time-dated pregnant rats were exposed to hypoxia (10.5% O2) from day 15 to 21 of gestation. Brain HI injury was determined in day 10 pups. Maternal hypoxia resulted in asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
96
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 52 publications
9
96
0
1
Order By: Relevance
“…In our study, we found that UPI-induced IUGR increased Sp1 binding to GR exon 1.7 promoter concurrently with Brg1 binding and increased GR exon 1.7 expression. In contrast, IUGR induced by maternal hypoxia in neonatal rats led to decreased hippocampal Sp1 binding to GR exon 1.7 promoter in association with decreased GR and exon 1.7 mRNA variant expressions (14). Taken together, these data suggest that Sp1 binding to GR exon 1.7 promoter is necessary for GR exon 1.7 transcription.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In our study, we found that UPI-induced IUGR increased Sp1 binding to GR exon 1.7 promoter concurrently with Brg1 binding and increased GR exon 1.7 expression. In contrast, IUGR induced by maternal hypoxia in neonatal rats led to decreased hippocampal Sp1 binding to GR exon 1.7 promoter in association with decreased GR and exon 1.7 mRNA variant expressions (14). Taken together, these data suggest that Sp1 binding to GR exon 1.7 promoter is necessary for GR exon 1.7 transcription.…”
Section: Discussionmentioning
confidence: 78%
“…The expression of the exon 1.7 variant is highly abundant in the hippocampus, but it is absent in other tissues (48). Exon 1.7 plays an important role in regulating hippocampus GR expression and programming the HPA axis sensitivity (14,48,50,77). Interestingly, UPI-induced IUGR specifically increases GR exon 1.7 mRNA variant expression in male rat pup hippocampus (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence from both human and animal studies indicates that epigenetic modifications serve as a memory of early life events and can induce long-term changes in gene expression profiles, which potentially result in disease in later life [8,13,14] (Figure 1). For example, in a recent study, epigenetic programming of the glucocorticoid receptor ( GR ) gene after maternal hypoxia was found to be related to the enhanced susceptibility of neonate hypoxic-ischemic encephalopathy (HIE) brain injury [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Maternal hypoxia also delays neuronal migration and alters neurotransmitters expression during embryogenesis [18], subsequently compromising neuronal circuits and affecting neural organization in the brain tissue [19]. As a result, maternal hypoxia leads to increased susceptibility to seizures, epilepsy [20], and cerebral insults in affected offspring [15,19]. However, the molecular mechanisms of gestational hypoxia in the programming of brain disorders in postnatal life remain largely elusive.…”
Section: Introductionmentioning
confidence: 99%